A comparative approach to testing hypotheses for the evolution of sex‐biased dispersal in bean beetles. Issue 21 (8th October 2015) - Downey, Michelle H.; Searle, Rebecca; Bellur, Sunil; Geiger, Adam; Maitner, Brian S.; Ohm, Johanna R.; Tuda, Midori; Miller, Tom E. X.
Abstract: Understanding the selective forces that shape dispersal strategies is a fundamental goal of evolutionary ecology and is increasingly important in changing, human‐altered environments. Sex‐biased dispersal (SBD) is common in dioecious taxa, and understanding variation in the direction and magnitude of SBD across taxa has been a persistent challenge. We took a comparative, laboratory‐based approach using 16 groups (species or strains) of bean beetles (genera Acanthoscelides, Callosobruchus, and Zabrotes, including 10 strains of one species) to test two predictions that emerge from dominant hypotheses for the evolution of SBD: (1) groups that suffer greater costs of inbreeding should exhibit greater SBD in favor of either sex (inbreeding avoidance hypothesis) and (2) groups with stronger local mate competition should exhibit greater male bias in dispersal (kin competition avoidance hypothesis). We used laboratory experiments to quantify SBD in crawling dispersal, the fitness effects of inbreeding, and the degree of polygyny (number of female mates per male), a proxy for local mate competition. While we found that both polygyny and male‐biased dispersal were common across bean beetle groups, consistent with the kin competition avoidance hypothesis, quantitative relationships between trait values did not support the predictions. Across groups, there was no significant association between SBD and effects of inbreeding nor SBD and degree of polygyny, using either raw values or phylogenetically independent contrasts. We discuss possible limitations of our experimental approach for detecting the predicted relationships, as well as reasons why single‐factor hypotheses may be too simplistic to explain the evolution of SBD. Abstract : Traits correlations across groups. A, C, Joint posterior means for (A) sex bias in dispersal (absolute value of the log ratio of female‐to‐male dispersal distance, indicating bias in either direction) and effect of inbreeding (proportional effect of inbreeding on offspring recruitment), and (C) sex bias in dispersal (signed value of the log ratio of female‐to‐male dispersal distance) and degree of polygyny (log number of female mates per male, or harem size). Locations of 4‐letter taxon symbols (Table 1) show bivariate means. B, D, Posterior probabilities for correlation between absolute dispersal bias and inbreeding effect (B) and signed dispersal bias and polygyny (D). Gray bars show the correlation of raw trait values, and unfilled bars show the correlation of the phylogenetically independent contrasts. Vertical dashed lines represent bounds of the 95% credible intervals for the correlations of raw trait values (gray) and phylogenetically independent contrasts (black).